Public governance-constraints and challenges for social work practice - Jessen, Jorunn Theresia (Journal of Comparative Social Work, 2015)
In the wake of public sector reforms, the work environment of professionals is changing; there is more description of results and outputs and tighter requirements of front-line work. The changes taking place address a shift towards managerial forms of control and organizational regulations in a range of Western countries. However, the new managerial regimes have different consequences for professionals as objects and subjects of governance. This paper investigates the extent of managerial and administrative regulations in the Norwegian social services, questioning the asserted negative impacts on professional autonomy in social work practice. The empirical data derive from a survey conducted among practitioners and managers in 125 local agencies, and compared to bureaucratic rules and agency procedures that set constraints, the new management model allows both autonomy and flexibility in choosing means and measures in various fields. Most of all, collegial support plays a significant role in providing professional standards for decision-making. The increase of management techniques and standard procedures in public administration concurrently challenges social work values, translating the social services into a field of more regulatory practices.